Reestructuración técnico administrativa de la empresa Domiflores (2021)
This project is developed within the company Domiflores, a florist located in the city of Bogotá, which has five locations and whose study will begin with a diagnosis, since the company has never performed an analysis of its internal processes or external, in this chapter we proceed to identify the shortcomings that it presents, and prioritize them for a complete study. Based on the information observed, a technical study is carried out that covers the issues to be solved, standardizing and improving processes, distributions and tools within the company. In the same way, the administrative aspects of the company will be analyzed giving an improvement in its structure and generating a strategic plan that allows the growth of the company together with the corrections of its deficiencies. Finally, a financial study will be carried out, in which the necessary investment for the implementation of the project will be evidenced, and the comparison between its current financial statements and those proposed, analyzing it through indicators in order to present the scenarios to the Domiflores company and from this way to reach a conclusion of continuous improvement of this.